PERSEPSI PENGUNJUNG TERHADAP PENYELENGGARAAN GARUDA INDONESIA TRAVEL FAIR DALAM MENDUKUNG KEGIATAN WISATA DI INDONESIA - Mertha, I Wayan; Andriastuti, Mutia (JURNAL KEPARIWISATAAN, 2016)
The purpose of this study is to analyse the perceptions of visitors to sales promotion activities in the implementation of Garuda Indonesia Travel Fair (GATF) conducted in JICC (Jakarta International Convention Centre), as well as their decision to visit tourism destinations as the impact of promotional activities. Distributed questionnaires with Likert scale of degree 5 that have been tested for validity and reliabelity the exhibition visitors for three days, and charged 272 eligible questionnaires were analyzed. Data were analyzed by quantitative descriptive. The results showed that the activity of sales promotion in the administration GATF and promotion of tourism destinations offered is considered good, and capable of forming a positive perception of visitors to support tourism activities in Indonesia, which means also that the promotional activities undertaken in the implementation of GATF able to influence the decision of visitors to the exhibition to visited tourism destination in Indonesia.